Seismic Vulnerability Assessment for Various Shapes and Types of Reinforced Concrete Shear Walls in Multi-Storey Buildings - Nayak, Chittaranjan Birabar; Jagadale, Umesh Tukaram; Thakare, Sunil Bhimro; Suryawanshi, Nagesh Tatoba; Kate, Gunavant Kashinath; Deulkar, Wasudeo Narayanrao (Proceedings of Engineering and Technology Innovation, 2022)
To improve the lateral stiffness and economy, reinforced concrete shear walls are introduced in buildings. This study aims to conduct the seismic assessment of shear walls in a multi-storey building. In this work, various factors are investigated and their performance is compared for various shapes and types of shear walls with respect to strength, displacement, time period, etc. The building considered for the study purpose is a G+12 residential building and is situated in a high seismic zone. The response spectrum analysis of the building is carried out by using the software ETABS. The results show that shear walls not only reduce the seismic forces in a building, but also are advantageous if they are situated in proper positions.